Prognostic Value of Pretreatment Red Blood Cell Distribution Width in Patients With Esophageal Cancer Who Underwent Esophagectomy: A Retrospective Study. Issue 2 (28th June 2022) - Yoshida, Naoya; Horinouchi, Tomo; Eto, Kojiro; Harada, Kazuto; Sawayama, Hiroshi; Imamura, Yu; Iwatsuki, Masaaki; Ishimoto, Takatsugu; Baba, Yoshifumi; Miyamoto, Yuji; Watanabe, Masayuki; Baba, Hideo
Abstract : Objective: This comprehensive analysis aimed to elucidate the mechanism underlying how high pretreatment red blood cell distribution width (RDW) reflects poor prognosis after esophagectomy for esophageal cancer. Background: Several cohort studies have reported that preoperative RDW might be a predictive marker for poor prognosis after esophagectomy; however, the underlying mechanism of this relationship has not been elucidated. Methods: This study included 626 patients with esophageal cancer who underwent esophagectomy between April 2005 and November 2020. A retrospective investigation of the association between pretreatment RDW and clinicopathological features, blood data, short-term outcomes, and prognosis was conducted using a prospectively entered institutional clinical database and the latest follow-up data. Results: Of 626 patients, 87 (13.9%) had a high pretreatment RDW. High RDW was significantly associated with several disadvantageous characteristics regarding performance status, the American Society of Anesthesiologists physical status, respiratory comorbidity, and nutritional status. Similarly, high RDW correlated with frequent postoperative morbidities (respiratory morbidity and reoperation; P = 0.022 and 0.034, respectively), decreased opportunities for adjuvant chemotherapy ( P = 0.0062), and increased death from causes other than esophageal cancer ( P = 0.046). Finally, RDW could be an independent predictor of survival after esophagectomy (hazard ratio, 1.47; 95% confidence interval, 1.009–2.148; P = 0.045). Conclusion: High pretreatment RDW reflected various adverse backgrounds and it could be a surrogate marker of poor prognosis in patients who have undergone esophagectomy for esophageal cancer. Abstract : Mini-abstract: This study comprehensively investigated the mechanism underlying how high red blood cell distribution width (RDW) reflects poor prognosis after esophagectomy for esophageal cancer. High pretreatment RDW reflected several disadvantageous backgrounds regarding patient's characteristics, nutritional status, morbidities, and adjuvant chemotherapy; thus, it could be a predictive marker for poor prognosis.